LRP1 involvement in FHIT-regulated HER2 signaling in non-small cell lung cancer - Théophile Ponchel; Emma Loeffler; Julien Ancel; Audrey Brisebarre; Nathalie Lalun; Véronique Dalstein; Anne Durlach; Gaëtan Deslée; Stéphane Dedieu; Myriam Polette; Béatrice Nawrocki-Raby (European Journal of Cell Biology)
The tumor suppressor fragile histidine triad (FHIT) is frequently lost in non-small cell lung cancer (NSCLC). We previously showed that a down-regulation of FHIT causes an up-regulation of the activity of HER2 associated to an epithelial-mesenchymal transition (EMT) and that lung tumor cells harboring a FHITlow/pHER2high phenotype are sensitive to anti-HER2 drugs. Here, we sought to decipher the FHIT-regulated HER2 signaling pathway in NSCLC. Transcriptomic analysis of tumor cells isolated from NSCLC revealed the endocytic receptor low density lipoprotein receptor-related protein 1 (LRP1), a central regulator of membrane trafficking and cell signaling, as a potential player of this signaling. In a cohort of 80 NSCLC assessed by immunohistochemistry, we found a significant association between a low FHIT expression and a high pHER2 and LRP1 expression by tumor cells. Experiments of FHIT silencing showed that FHIT regulated LRP1 expression both at the mRNA and protein levels in lung cell lines. Analyzing the relationship between LRP1 and HER2, we observed that an anti-HER2 targeted therapy reversed LRP1 overexpression induced by FHIT silencing whereas LRP1 silencing did not affect HER2 activity. Studying the functional role of LRP1, we showed that cell proliferation and invasion induced by FHIT silencing were LRP1-dependent. In addition, we found that the induction of vimentin upon FHIT inactivation was counteracted by LRP1 silencing. These results suggest that LRP1 acts downstream of HER2 to induce EMT and tumor progression following FHIT loss. Dual targeting of HER2 and LRP1 might represent a therapeutic strategy to more efficiently inhibit HER2 signaling in FHIT-negative NSCLC.